SOSIALISASI KEMASAN PRODUK SEBAGAI UPAYA MENINGKATKAN DAYA SAING BAGI UMKM DI DESA FIRDAUS - Yumna Nada Yusli,; Adrial Falahi, (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2022)
Expanding the distribution of product sales to shops in Firdaus Village is a challenge for UMKM. Especially if the MSME product does not have attractiveness and selling value because it does not have a brand name, packaging that has no selling value, and has not yet obtained a PIRT permit. The limitations of UMKM in using technology to support operations and marketing are also still an obstacle. This packaging socialization activity aims to provide understanding and assist UMKM in order to increase the attractiveness and selling value of the product so that it can be accepted by the shops around. In addition, this activity aims to help partners improve their capabilities in terms of knowledge and technical related to the use of technology so that later it can be useful for operations and product promotion. The results of this activity are the formation of brand names and product labels, the creation of innovative, attractive, and contemporary packaging, obtaining a PIRT certificate to make the product successfully accepted in stores. This product packaging socialization activity also increases the skills of UMKM in using technology to purchase production materials. After the marketing socialization activity and the mentoring period are over, it is hoped that it can provide benefits for UMKM to independently expand product distribution to shops around Firdaus Village so as to increase sales and the family economy